“Pedras, Noites e Poemas”: Mulheres em Luta na Amazônia Maranhense - SANTOS, Francisca Regilma de Santana (2021)
The objective of this research was to analyze the strategies constructed by, and among, women in the processes of fighting for land and territory, in the Amazon region, in the State of Maranhão, from of the narratives of indigenous women, landless and babassu coconut breakers, with the purpose of to make their experiences, times and knowledge visible. We take as guidelines the following questions: How do women experience the processes of fighting for land and territory in Amazon Maranhão? What are the practices of re-existence built by them in these Law Suit? At the present time, these re-existences are directed towards which issue(s)? As a methodology, we used ethnography and oral history (PORTELLI, 2016; ALBERTI, 2005) and the use of in-depth interviews as a means of obtaining narratives, in addition to bibliographic and virtual research. To understand the context and place of the struggle of these women, we use the border category, based on Martins (2018) and Becker (1988, 2015a and 2015b) in dialogue with decolonial perspectives (QUIJANO, 2005; MIGNOLO, 2003; LUGONES, 2014), on the coloniality and decoloniality of power, being, and genre. We use the point of view category (COLLINS, 2019) and everyday forms of peasant resistance (SCOTT, 2002). We take into account the intersectionality (AKOTIRENE, 2019) of the multiple conditions of subalternity experienced by these women. This is necessary because these categories, when addressed separately, do not include women. In this sense, we saw that the strategies of struggle for land and territory in Amazon region of Maranhão are varied, and it is the female bodies that are ahead of the more distinct processes, defending the right to land and life of peoples and territories; facing machismo, violence, inequalities as well as articulating, internally and in articulation networks. By fighting for land and territory they engender daily and politically anti-capitalist, consequently anti-racist and anti-patriarchal, from the same place of enunciation and different places of speech.